Character Identification in a Breastless Novel by Betty Sitorus - Yosef Demon; Sehandi Yohanes (Randwick International of Education and Linguistics Science Journal, 2023)
Factual social phenomena related to life and human life are a source of inspiration that never runs dry for a writer of literary works. The Novel Breastless by Betty Sitorus is a work of fiction based on the fact that cancer sufferers are suffering. This study seeks to reveal how the main character in the novel Breastless by Betty Sitorus fights cancer? Thus the purpose of this study is to identify the main character in the novel Breastless Betty Sitorus' work against cancer. The approach used is a qualitative approach the research method used is the library method and is enhanced by reading, note-taking and underlining techniques. The theory used is the theory of Literary Psychology. The results of this study prove that the main character in the novel Breastless Betty Sitorus' works include a number of characters such as shock, anxiety, fear, compassion, patience, optimism, alertness, belief in traditional medicine, confidence, and positive thinking.